An evaluation on the financial performance: a case study of Telekom Malaysia Berhad / Nik Noor Ashikin Nik Alias - Nik Alias, Nik Noor Ashikin (Faculty of Business and Management, 2010)
This study was carried out to determine performance of accompany is trough ratio analysis for the 5 years. The company of Telekom Malaysia Berhad was chosen as the company analysis. Telekom Malaysia Berhad is a telecommunication company in Malaysia is under the services. All the information I get from Annual Report in 2005, 2006, 2007, 2008 and 2009. The factors that determine the best types of company are different from those that determine the best type of stock. In contrast, the stock of an organization company may have a market price below its in transit value and may thus make a good investment. Common way of measuring the performance of a company is through ratio analysis. Ratio analysis is concerned with finding relationship between components found in the balance sheet and profit and loss account of the company. Ratio analysis is basically like a thermometer. It reads the temperature of a company. In this case, it is reading the health of a company. By findings the relationships in the components, I hope to detect some unusual deviations from the norm. This would trigger further investigation; thus, ratio analysis is only a means of checking the health or performance of a company. This evaluation is to analyze a Telekom Malaysia’s financial position and performance and to access future financial performance. It consists three broad areas which are profitability analysis, risk analysis and analysis of sources and uses of funds. Profitability analysis is the evaluation of Telekom Malaysia’s return on investment and focuses on Telekom Malaysia’s sources and level of profits while the risk analysis is to evaluate the Telekom Malaysia’s ability to meet its commitment. The analysis of sources and uses of funds are to evaluate how the Telekom Malaysia Berhad is obtaining and deploying its funds.